Adsorption behaviour of surfactant-nanoparticles at the gas-liquid interface: Influence of the alkane chain length. (12th October 2019) - Zhao, Mingwei; Wang, Ruoyu; Dai, Caili; Wu, Xuepeng; Wu, Youran; Dai, Yingjie; Wu, Yining
Graphical abstract: Highlights: CGMD found an asymmetric Janus structure forming at interface by surfactant-NP. The adsorption of modified NPs at interface change the interfacial properties. Stability of surfactant-NPs foam increased with increasing surfactant chain length. Abstract: Silica nanoparticles (NPs) have shown tremendous application potential as stabilising agents in foams. The adsorption of cationic surfactants on the surface of NPs through electrostatic interactions forms integrated surfactant-NP compounds and endows the NPs with surfactancy. The aim of this study was to investigate the influence of the alkane chain length of cationic surfactants on NP surfactancy and foam stability. The results demonstrate that the surface tension decreases and dilational elasticity modulus increases with surfactant chain length. Simultaneously, coalescence of bubbles is markedly suppressed and the stability of surfactant-NP foams is enhanced in static and dynamic tests. With a coarse-grained molecular dynamics simulation (CGMD), it was found that the surfactant-NP complexes evolve into an asymmetric Janus structure at the gas-liquid interface from their symmetric configuration in the aqueous phase. In addition, the resistance force during the pulling of a NP away from the interface increases with surfactant chain length. The simulation results imply that surfactant-NPs have a high surfactancy and the adsorption stability is improved with increasing surfactant chain length, which is in good agreement with the experimental results.